2017
DOI: 10.20538/1682-0363-2017-4-30-41
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of development of antipsychotic-induced metabolic disorders: pharmacogenetic aspect

Abstract: Основными препаратами для терапии психи-ческих расстройств шизофренического спектра являются антипсихотики, требующие длитель-ного применения. Антипсихотические препараты * Насырова Регина Фаритовна, e-mail: reginaf@bekhterev.ru. УДК 615.214.21-06:616-008.9 DOI: 10.20538/1682УДК 615.214.21-06:616-008.9 DOI: 10.20538/ -0363-2017 Для цитирования: Насырова Р.Ф., Толмачев М.Ю., Сычев Д.А., Яхин К.К., Незнанов Н.Г. Механизмы развития антипси-хотик-индуцированных метаболических нарушений: фармакогенетический аспек… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…(5) FGAs are characterized by extrapyramidal symptoms, and hyperprolactinemia and, to a lesser extent, metabolic disorders; SGAs are more associated with weight gain, the appearance of type 2 diabetes, cardiovascular diseases, and the development of MetS. (6,7) Results of numerous studies show that antipsychotic induced weight gain occurs in 12-16 weeks. (8) It was found that patients with psychotic disorders are more likely to suffer from obesity than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…(5) FGAs are characterized by extrapyramidal symptoms, and hyperprolactinemia and, to a lesser extent, metabolic disorders; SGAs are more associated with weight gain, the appearance of type 2 diabetes, cardiovascular diseases, and the development of MetS. (6,7) Results of numerous studies show that antipsychotic induced weight gain occurs in 12-16 weeks. (8) It was found that patients with psychotic disorders are more likely to suffer from obesity than the general population.…”
Section: Introductionmentioning
confidence: 99%